The effect of perceived usefulness, perceived ease of use, and perceived risk on behavioral intention to use e-money - Nezha Vitri Amira; Perengki Susanto (Operations Management and Information System Studies, 2021)
This study aimed to determine: (1) the effect of perceived usefulness on behavioral intention (2) the effect of perceived ease of use on behavioral intention (3) the effect of perceived risk on behavioral intention to use E-Money in Padang. The type of research used was quantitative research design model with purposive sampling as the sampling technique involving a total of 208 respondents of E-Money users in Padang. This study used primary data distributed to E-Money users in Padang who had an interest in using E-Money. The analytical method used was descriptive and quantitative analysis through multiple regression on SPSS 16.0 software. The results of the study were: (1) perceived usefulness had a significant effect on behavioral intention; (2) perceived ease of use had a significant effect on behavioral intention; (3) perceived risk had a significant effect on behavioral intention on interest in using E-Money in Padang.